Factors determining customers’ repurchase intention of healthcare insurance products in Malaysia - Rahman, Muhammad Sabbir; Mohamad, Osman; AbdelFattah , Fadi AbdelMuniem; Aziz, Nusrtae (2014)
This inquiry studies the empirical testing the determinant of customers’ behaviour towards the healthcare insurance products in Malaysia. The research was established on an empirical investigation of the existing healthcare insurance customers from Klang valley, Malaysia. The main data for the study were generated from self-administered survey of 160 respondents. Data were analysed using descriptive and inferential statistics (Exploratory Factor Analysis). From the application of exploratory factor analysis, it was concluded that the correlation matrix was all positive and above 0.6. Three factors were extracted which explain 47% of the variation. Lastly, the studied variables were loaded in one domain or another confirming suitability for further analysis. As the survey is based on healthcare insurance in particular from Malaysian customers’ perspective, the findings would be of interest to the managers of health insurance providers as well as policy makers to draw future strategies for development.